Biocontrol Potential of Endophytic Streptomyces malaysiensis 8ZJF-21 From Medicinal Plant Against Banana Fusarium Wilt Caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 - Zhang, Lu; Liu, Ziyu; Wang, Yong; Zhang, Jiaqi; Wan, Shujie; Huang, Yating; Yun, Tianyan; Xie, Jianghui; Wang, Wei (Frontiers in Plant Science, 2022)
Banana (Musa spp.) is an important fruit crop cultivated in most tropical countries. Banana Fusarium wilt caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is the most destructive fungal disease. Biocontrol using endophytic microorganisms is considered as a safety and sustainable strategy. Actinomycetes have a potential for the production of diverse metabolites. Isolation of endophytic actinomycetes with high efficiency and broad-spectrum antagonism is key for exploring biocontrol agents. Our previous study showed that a total of 144 endophytic actinomycetes were isolated from different tissues of medicinal plants in Hainan, China. Especially, strain 8ZJF-21 exhibited a broad-spectrum antifungal activity. Its morphological, physiological, and biochemical characteristics were consistent with the genus Streptomyces. The phylogenetic tree demonstrated that strain 8ZJF-21 formed a distinct clade with Streptomyces malaysiensis. Average nucleotide identity (ANI) was 98.49% above the threshold of novel species. The pot experiment revealed that endophytic Streptomyces malaysiensis 8ZJF-21 could improve the plant resistance to Foc TR4 by enhancing the expression levels of defense-related and antioxidant enzyme genes. It also promoted the plant growth by producing several extracellular enzymes and metabolites. Antifungal mechanism assays showed that S. malaysiensis 8ZJF-21 extract inhibited mycelial growth and spore germination of Foc TR4 in vitro. Pathogenic cells occurred cytoplasmic heterogeneity, disappeared organelles, and ruptured ultrastructure. Sequencing and annotation of genome suggested that S. malaysiensis 8ZJF-21 had a potential of producing novel metabolites. Nineteen volatile organic compounds were obtained from the extract by Gas Chromatography-Mass Spectrometry (GC-MS). Hence, endophytic Streptomyces strains will become essential biocontrol agents of modern agricultural practice.